The World View of W.S. Rendra in Empat Kumpulan Sajak Structuralism Genetic Review - Shofi, Moh. Shofiuddin; Doyin, Mukh (Pascasarjana Universitas Negeri Semarang, 2018)
Poetry becomes one of poets’ media to deliver aspiration, notion, even ideologies. One of the poets who were able to share his notion, feeling even reality well was W.S. Rendra. The purpose of the research is to describe his point of view of world express into Four Poetry Sets. The data of the research is excerpts which have relevancy to problem symptom, the data is gained through understanding the text and literature studies. The review toward W.S. Rendra’s work titled Empat Kumpulan Sajak using literature sociology approach, Goldmann genetic Structuralism theory. Through genetic Structuralism, the theory can be seen completely how the point of view of a poet. The findings are some factors of humanism affecting the poetries in Empat Kumpulan Sajak. Besides the fact of humanity, there is also a point of view of W.S Rendra about compassion, nature, and patriotism. The benefit for readers is they can get and understand W.S. Rendra’s point of view expressed through Empat Kumpulan Sajak.